Application of the International Classification of Functioning, Disabilities and Health in the Rehabilitation Process - Galina E. Ivanova; Maria A. Bulatova; Boris B. Polyaev; Alexandra K. Trofimova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
With the development of high technologies in medicine, the diagnostic process is improving, the methods of treating patients are refining, the percentage of patients who survived after serious injuries, diseases and/or conditions is increasing. The issue of the patients` quality of life that received primary medical, specialized, including high-tech medical care is becoming a priority for health care. Rehabilitation is defined as one of the critical interventions "enabling people with disabilities to achieve and maintain maximum independence, full physical, mental, social and professional ability and full inclusion and participation in all aspects of life". The problems and prospects of rehabilitation medicine for the future arise due to critical changes in demographics, life expectancy, a variation in approaches to assessing disability, an increase in the prevalence of long-term health disorders, especially in connection with the new coronavirus infection, technological progress, as well as changes in health care costs and changes in society's requirements for well-being and quality of life, including health. The object of the study is the process of organizing medical rehabilitation of patients with cerebral stroke at the second phase of rehabilitation process in a 24-hour inpatient medical rehabilitation department for patients with impaired function, structures, limited activity and participation due to damage to the central nervous system based on the application of the International Classification of Functioning, Disabilities and Health (ICF) for the rehabilitation diagnosis description (the degree of disturbance of structure, function, limitation of activity and participation, the degree of influence of environmental factors) and the formation of the medical rehabilitation program on its basis.